CAMBODIAN HIGH SCHOOL STUDENTS’ MOTIVATION TOWARD LEARNING ENGLISH - Sreynich Sor; Sreyni Chorn; Seynich Dean; Sereyrath Em (PROJECT (Professional Journal of English Education), 2022)
This present study explored the motivation levels and motivation types of Cambodian high school students learning English. With a focus on Hun Sen Peam Ro high school in Prey Veng province, the data was gathered using a quantitative approach. The study's objectives were to determine to what extent the students were motivated to learn English, to determine whether their motivation was more intrinsic or extrinsic, and to determine whether there was a statistically significant difference between the motivation levels of male and female students. 265 students attended the study. As a result, it was indicated that the students were highly motivated to learn English, and they were more extrinsically motivated than intrinsically. It was also noted that female students had a statistically higher extrinsic motivation than male students did. The current study suggests that intrinsic and extrinsic motivation must be interrelated because overall motivation is essential for students’ success in learning English. Finally, future studies should be conducted with larger sample size and at other educational institutions across the country using other statistical analyses. Qualitative and mixed-methods designs are also recommended. Keywords:  Cambodia, High School Students, MoEYS, Motivation, Male and Female Students